Stingless bees (Tribe Meliponini) in Latin American agroecosystems - Real-Luna, Natalia; Rivera-Hernández, Jaime Ernesto; Alcántara-Salinas, Graciela; Rojas-Malavasi, Geovanna; Morales-Vargas, Ana Paulina; Pérez-Sato, Juan Antonio (Revista Mexicana de Ciencias Agrícolas, 2022)
Meliponines are important pollinators of wild and cultivated plants in Latin America. In addition, these bees have the characteristics of a bioindicator, information necessary to develop conservation and sustainable management strategies for species of cultural, ecological, and economic importance. The objective of this work is to determine the species of meliponines that pollinate agroecosystems in Latin America and their use as bioindicators, which will serve as the basis for implementing strategies for the conservation and sustainable management of these bees. This research used sources of information related to the meliponines present in Latin America, crops they pollinate and the use of these stingless bees as bioindicators. Forty-six crops pollinated by meliponines in eight countries were recorded, where 17 genera and 54 species were recorded, with Brazil being the country with the highest record with 33 crops. Meliponines contribute directly to the pollination of agroecosystems, improving yield and quality, therefore it is important to establish strategies for conservation of these bees, such as maintaining flower patches that serve as food throughout the year. The protection of stingless bees is necessary because of the importance they have in the pollination service; however, it is also needed to conduct more research on their biology and their use in greenhouses, in addition to their usefulness as bioindicators.
Keywords: bioindicators; meliponines; pollinators